pgmcc a TCP-friendly single-rate multicast congestion control scheme. - Rizzo, Luigi
We present a single rate multicast congestion control scheme (pgmcc) which is TCP-friendly and achieves scalability, stability and fast response to variations in network conditions. pgmcc is suitable for both non-reliable and reliable data transfers; it uses a window-based TCP-like controller based on positive ACKs and run between the sender and a group's representative, the acker. The innovative part of pgmcc is a fast and low-overhead procedure to select (and track changes of) the acker, which permits us to consider the acker as a moving receiver rather than a changing one. As such, the scheme is robust to measurement errors, and supports fast response to changes in the receiver set and/or network conditions. The scheme has been implemented in the PGM protocol, and the paper presents a number of experimental results on its performance.
Keywords: Computer systems organization; Computer communication networks; Network protocols; TCP IP; Hardware; Input output and data communications; Input output devices; Channels and controllers; Computer systems organization; Mathematics of computing; Discrete mathematics; Computing methodologies; Artificial intelligence; Problem solving, control methods and search; Control theory; Design; Experimentation; Measurement; Performance; Reliability; Standardization; Theory